PENGARUH KONSELING KELOMPOK MELALUI PENDEKATAN RASIONAL EMOTIF BEHAVIOR THERAPY (REBT) UNTUK MENGURANGI KECEMASAN SISWA MENGHADAPI UJIAN DI SMP - Sholikhul Huda; Denok Detiawati; Bisri Ekhsan (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The purpose of this study is to understand the effectiveness of REBT technique in lowering student anxiety levels during PTS in SMPN 1 Lamongan. There are ten students who experience tingkat tinggi as a subyek of research. The data collection method employs Likert scales. The T-test is a statistical analysis technique that uses uji. Based on the results of the analysis of the variance of the two groups, which are not homogeneous, T hitung 9.590 in the derajat kebebasan (df) 9 and then compared with ttabel 0,05 = 2.262, which indicates that hitung exceeds ttabel (9.590 ≥ 2.262). This indicates that Ho is tolak and Ha is diterima. This indicates that after implementing the REBT, there is a pengurangan kecemasan among the students. Researchers concluded that teachers, in particular, must constantly innovate in the classroom in order to improve student performance.